Effect of supplementation of micronutrients through different sources on the production performance in crossbred dairy cows - GOWDA, N K S; PRASAD, C S; RAMANA, J V (The Indian Journal of Animal Sciences, 2014)
Study was conducted to know the lactation performance in 12 crossbred cows fed diets with inorganiC and organic source of micronutrient supplementation under each of the dietary treatment. Cows in group 1 were fed concentrate mixture supplemented with 1 % commercial mineral mixture, whereas cows in group 2 were fed with additional green fodder as a strategic supplement in place of 1 % inorganic mineral mixture to meet the mineral needs for 120 days. There was no significant difference in the total dry matter intake in both the groups (10.7S and 10.41 kg). The average daily intake of Ca (55.23 and 41.96 g), Cu (173.19 and 137.10 mg), Zn (800,70 and 625.39 mg) and Mn (1147.49 and 924.11 mg) was significantly (P